Analysis of Classical Time-Trial Performance and Technique-Specific Physiological Determinants in Elite Female Cross-Country Skiers - Sandbakk, Øyvind; Losnegard, Thomas; Skattebo, Øyvind; Hegge, Ann M.; Tønnessen, Espen; Kocbach, Jan (Frontiers in Physiology, 2016)
The present study investigated the contribution of performance on uphill, flat, and downhill sections to overall performance in an international 10-km classical time-trial in elite female cross-country skiers, as well as the relationships between performance on snow and laboratory-measured physiological variables in the double poling (DP) and diagonal (DIA) techniques. Ten elite female cross-country skiers were continuously measured by a global positioning system device during an international 10-km cross-country skiing time-trial in the classical technique. One month prior to the race, all skiers performed a 5-min submaximal and 3-min self-paced performance test while roller skiing on a treadmill, both in the DP and DIA techniques. The time spent on uphill (r=0.98) and flat (r=0.91) sections of the race correlated most strongly with the overall 10-km performance (both p<0.05). Approximately 56% of the racing time was spent uphill, and stepwise multiple regression revealed that uphill time explained 95.5% of the variance in overall performance (p<0.001). Distance covered during the 3-min roller-skiing test and body-mass normalized peak oxygen uptake (VO2peak) in both techniques showed the strongest correlations with overall time-trial performance (r=0.66-0.78), with DP capacity tending to have greatest impact on the flat and DIA capacity on uphill terrain (all p<0.05). Our present findings reveal that the time spent uphill most strongly determine classical time-trial performance, and that the major portion of the performance differences among elite female cross-country skiers can be explained by variations in technique-specific aerobic power.